2019
DOI: 10.35592/jrb.v2i1.258
|View full text |Cite
|
Sign up to set email alerts
|

Inovasi UMKM Boga Tradisional Dalam Mencapai Keunggulan Bersaing

Abstract: Empowerment of Small and Medium Enterprises (SMEs) becomes very strategic, because of its huge potential in driving the economic activities of the community and at the same time being the foundation of the income sources of some people in improving their welfare. But there are still many problems faced by Indonesian SMEs, some of which include competitiveness of MSMEs in national and global markets. The low competitiveness of these SMEs as expressed by Kumorotomo (2008), is due to the large number of problems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
3
0
2
Order By: Relevance
“…Product innovation and process innovation are positively related to SME performance (Ar & Baki, 2011;Hilmi et al, 2010;Umar et al, 2018;Al-Sa' di et al, 2017). In addition, product innovation and process innovation, combined with marketing innovation and/or organizational innovation, are positively related to SME performance (Hafeez et al, 2013;Kiveu et al, 2019;Noor et al, 2019). Therefore, it can be concluded that the hypothesis is as follows:…”
Section: The Relationship Of Innovation To Sme Performancementioning
confidence: 95%
See 2 more Smart Citations
“…Product innovation and process innovation are positively related to SME performance (Ar & Baki, 2011;Hilmi et al, 2010;Umar et al, 2018;Al-Sa' di et al, 2017). In addition, product innovation and process innovation, combined with marketing innovation and/or organizational innovation, are positively related to SME performance (Hafeez et al, 2013;Kiveu et al, 2019;Noor et al, 2019). Therefore, it can be concluded that the hypothesis is as follows:…”
Section: The Relationship Of Innovation To Sme Performancementioning
confidence: 95%
“…There are various indicators used in measuring innovation (Narsa, 2018;Herlinawati & Machmud, 2020;Noor et al, 2019;Novia et al, 2020). Among the many indicators, product innovation and process innovation are the types that are most often used in the study of innovation in SMEs (Umar et al, 2018).…”
Section: Innovationmentioning
confidence: 99%
See 1 more Smart Citation
“…Kemampuan melakukan inovasi bagi usaha mikro sangat dibutuhkan agar mampu mengatasi salah satu masalah daya saing usaha mikro Indonesia, karena merupakan salah komponen usaha yang memiliki kontribusi yang paling besar bagi perekonomian Indonesia. Namun di sisi lain UMKM memiliki kelemahan dalam manajemen sehingga perlunya upaya untuk memperbaikinya bagi peningkatan daya saing nasional dan global (Savitri Noor et al, 2019).…”
Section: Pendahuluanunclassified
“…Selanjutnya untuk memiliki keunggulan bersaing perusahaan dapat melakukan inovasi yang mengarah pada penciptaan nilai bagi pelanggan. Inovasi adalah sebuah proses yang dimulai dengan sebuah ide, diikuti dengan pengembangan sebuah penemuan, dan hasilnya adalah perkenalan produk, proses, atau jasa baru kepasar (Noor et al, 2019). Respon konsumen terhadap inovasi dan diversifikasi produk gula aren sangatlah penting.…”
Section: Pembahasanunclassified